Analisis Kesehatan PT. Bank Muamalat Indonesia, Tbk. Dengan Menggunakan Metode RGEC (Risk Profil, Good Corporate Governance, Earnings, Capital) Periode 2013-2021 - ZULFA ELIZA ZIAUDDIN; Tia Risnaini (JIM: Jurnal Ilmiah Mahasiswa, 2022)
ABSTRACT This study aims to determine the health condition of Bank Muamalat Indonesia for the period 2013-2021 in terms of each aspect of the RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital). The variables used are risk profile as measured by the ratio of NPF and FDR, Good Corporate Governance is measured through the results of self-assessment, earnings are measured by the ratio of NOM, ROA, ROE, BOPO, and capital is measured by the CAR ratio. This study uses descriptive analysis with a quantitative approach. The population in this study is the financial statements of Bank Muamalat Indonesia and the sample used is 64 data on te the financial ratios of Bank Muamalat Indonesia. The data used in this research is secondary data. Data collection techniques using documentation techniques. The results of the study indicate that the financial performance of Bank Muamalat Indonesia for the period 2013-2021 in terms of the Risk Profile aspect, which is in adequate condition. Aspects of Good Corporate Governance through the results of self-assesment are quite adequate. For the Earnings aspect, it is inadequate and for the Capital aspect, it is very adequate. The composite rating obtained by Bank Muamalat Indonesia for the nine years in 2013 was 72.5% with a rating of (healthy), in 2014 it was 62.5% with a rating of 3 (fairly healthy), in 2015 it was 52.5% with rank 4 (unhealthy), in 2016 it was 52,5% with a rank of 4 (unhealthy), in 2017 it was 52.5% with a rank of 4 (unhealthy), in 2018 it was 55% with a rank of 4 (unhealthy), in 2019 it was 55% with a rating of 4 (unhealthy), in 2020 it was 50% with a rating of 4 (unhealthy), and in 2021 it was 60% with a rank of 4 (unhealthy).